Predictors of thrombosis in children receiving therapy for acute lymphoblastic leukemia: Results from Dana‐Farber Cancer Institute ALL Consortium trial 05‐001. Issue 8 (22nd March 2022) - Athale, Uma H.; Flamand, Yael; Blonquist, Traci; Stevenson, Kristen E.; Spira, Menachem; Asselin, Barbara L.; Clavell, Luis A.; Cole, Peter D.; Kelly, Kara M.; Laverdiere, Caroline; Leclerc, Jean‐Marie; Michon, Bruno; et al.
Abstract: Background/objectives: Although thromboembolism (TE) is a serious complication in patients with acute lymphoblastic leukemia (ALL), thromboprophylaxis is not commonly used due to the inherent bleeding risk in this population. Identifying prothrombotic risk factors will help target thromboprophylaxis to those at highest thrombotic risk. We aimed to define predictors and the impact of TE on ALL outcome in children (1‐18 years) treated on the Dana‐Farber Cancer Institute ALL 05‐001 trial. Methods: Clinical and laboratory data including TE events were prospectively collected. PCR‐based allelic discrimination assay identified single‐nucleotide polymorphisms (SNP) for prothrombin G20210A (rs1799963) and Factor V G1691A (rs6025). Univariate and multivariable competing risk regression models evaluated the effect of diagnostic clinical (age, sex, body mass index, ALL‐immunophenotype, risk group) and laboratory variables (presenting leukocyte count, blood group, SNPs) on the cumulative incidence of TE. Cox regression modeling explored the impact of TE on survival. Results: Of 794 patients [median age 4.97 (range, 1.04‐17.96) years; males 441], 100 developed TE; 25‐month cumulative incidence 13.0% (95% CI, 10.7%‐15.5%). Univariate analyses identified older age (≥10 years), presenting leucocyte count, T‐ALL, high‐risk ALL, and non‐O blood group as risk factors. Age and non‐O blood group were independent predictors of TE on multivariable regression; the blood group impact being most evident in patients 1‐5 years of age ( P  = 0.011). TE did not impact survival. Induction TE was independently associated with induction failure (OR 6.45; 95% CI, 1.64‐25.47; P  = 0.008). Conclusion: We recommend further evaluation of these risk factors and consideration of thromboprophylaxis for patients ≥10 years (especially those ≥15 years) when receiving asparaginase.